PREPARATORY WORK FOR PERFORMANCE-BASED ASSESSMENT IN A LINGUISTICS COURSE AT HAI PHONG UNIVERSITY - Thu, Dinh Minh (VNU Journal of Foreign Studies; Vol 33 No 3DO - 10.25073/2525-2445/vnufs.4158, 2017)
The article discusses the significant contributors to a teacher's preparation for performance-based assessment (PBA) toward learners' success in achieving both the deep knowledge of a linguistics subject and the 21-century skills for English majors at Haiphong University. Through the literature review and document analysis, the pre-implementation process is approached in four major steps that the author adapts from the perspectives proposed by Brown (2003), VanTasselBaska (2013) and Espinosa (2015): (1) identifying learning outcomes, (2) building the rubric, (3) designing PBA tasks, and (4) supporting the learners. The learners’ socio-psychological identity is identified and the nature of the linguistics subjects is depicted in order to enable smooth assistance. The research mainly employs McTighe’s (2014) framework and Bloom taxonomy to determine the learning outcomes. Also, another McTighe’s (2014) framework is used as the basis to develop the rubric. Through the discussed points, this original research will dedicate to EFL Vietnamese learners’ success in PBA through a sophisticated threshold with deep awareness of enhancing learners’ learning of not only the knowledge but also the 21st-century skills for their future career. Furthermore, it is expected to fill in the gap in the ELT teachers in the regional community as a source of reference.